Estudo das vibrações transversais em um sistema viscoelástico acoplado de duas cordas - Rodrigues, Vinicius Weide (2013)
In this work, it is developed a study of the transverse vibrations of a system composed by two parallel strings of equal length, coupled by a viscoelastic element. The frequencies and mode shapes are obtained using modal analysis and a block matrix formulation for the system. The mode shapes are written by the dynamic basis, composed by the solution of a second order problem with impulsive initial conditions, and its first derivative. In the undamped case, different cases of the problem are considered by varying the parameters of the strings. The orthogonality of the mode shapes and the impulse response matrix are used to solve the undamped forced case. In the damped case, it is considered again the matrix formulation and use dynamic basis, and we present an uncoupled problem from simplifications of the system parameters. The damped forced vibrations are studied using the adjoint modal method, from which there is an orthogonality between the mode shapes of the original system and the mode shapes of the adjoint system associated, allowing the uncoupling and solvability of the system. The forced response is determined by using the matrix fundamental response.